Analyzing the effect of derivatives on the financial soundness of commercial banks in Italy: An approach based on the CAMELS framework. Issue 3 (25th April 2018) - Keffala, Mohamed Rochdi
Abstract: Italian economy is among the biggest economies in the Europe which suffered from the repercussions of the global financial crisis during this last decade. The weakness of Italian banking system coincides with the common debate about the implication of derivatives in the distress of banks' soundness. Thus, the aim of our research is to examine the effect of derivative instruments on the banks' soundness in Italy. To reach our goal, the CAMELS approach is employed to define the soundness of Italian commercial banks. To overcome the endogeneity issue of variables, an appropriate econometric procedure, namely the dynamic Generalized Method of Moments (GMM system) is applied using data from 22 commercial banks in Italy over the period 2005–2015. Explanatory variables are defined by derivative instruments (forwards, swaps, options, and futures), bank‐specific variable (bank's size as non‐CAMELS variable), industry‐specific variables (CR3, CR5, and HHI as indicators of bank's sector and market concentrations), and country‐specific variables (GDP and inflation). The main results reveal that the majority of the CAMELS indicators are favorably affected by derivative instruments especially forwards and options. The most important conclusion is that using derivative instruments does not threaten the financial soundness of commercial banks in Italy. As major implication decision‐makers and experts—after the global financial crisis—should not consider derivatives in part as responsible of the fragility of the Italian banking system.